Faktor-Faktor Yang Mempengaruhi Minat Wajib Pajak Terhadap Penggunaan E-Samsat - Kadek Wulandari Laksmi P; Ni Wayan Lasmi (Program Studi Akuntansi FPEB UPI, 2022)
This study aims to determine the factors that affect the interest of taxpayers in using e-Samsat as a medium for payment of Motor Vehicle Tax. The population in this study were motor vehicle taxpayers in Denpasar City who were registered at the joint office of Denpasar City. The sampling method used accidental sampling linear regression through SPSS. The results of the study state that perceived ease of use and subjective norms have a positive and significant effect on the interest in using e-Samsat. Meanwhile, perceived usefulness, attitude and perceived behavior control do not have a significant effect on the interest in using e-Samsat.